Indicadores de sustentabilidade da pecuária de corte no Cerrado e na Amazônia - Raphael Amazonas Mandarino (2016)
The general objective of this work was to study the sustainability indicators of crop production systems in the Cerrado and Amazon Biome. The study carried out in the Cerrado biome involved the evaluation of three different integrated production systems. The variables analyzed as indicators of sustainability were the emission of enteric methane, weight gain and the ratio between enteric methane emission and indicators of dry matter intake and performance of Nellore heifers (279 kg ± 21.4 live weight) in the different systems. The forage used was Brachiaria brizantha cv. BRS Piatã and arboreal species Eucalyptus urogrillis (Eucalyptus grandis x E. urophylla) planted in the north-south orientation, with treatments: ILP1 - forage cultivated with one year of formation under ILP system; ILP6 - forage cultivated with six years of training under a well managed ILP system over the years and; ILPF1 - forage with one year of formation via ILPF, cultivated in eucalyptus understory with spacing between rows of 22 m (417 trees.ha-1). In addition to the mentioned indicators, the dry mass and the leaf: stem ratio of the pasture were evaluated in dry and rainy seasons. The experimental design was completely randomized in factorial scheme 3 (treatments) for 2 (periods). The evaluations were conducted from April 2013 to May 2014. Heifers raised in ILP6 emitted more methane per kilogram of ingested dry matter and, consequently, presented greater losses of gross energy of the diet in the was of methane (6,15% in the dry and 8.65% in the rainy season). Comparing integrated systems both with first year pasture, the presence of trees (ILPF1) did not provide significant increases in animal weight gain. On the other hand, the weight gain per area (kgPV.ha-1) in the ILP1 system was 54% higher than the others in the dry season and 47% higher than ILPF1 in the waters. Enteric methane emissions were affected by the periods of the year, with higher gross emissions (g / day and kg / year) for the rainy season. It was concluded that the integrated systems, based on first-year pasture (with 1 year of training) were more efficient, since they presented lower values for the indicators energy loss of the diet via enteric fermentation (Ym) and emission of CH4 per kg of dry matter ingested. The objective of the second study was to evaluate the impact of the implementation of Good Agricultural Practices (GAP) projects on indicators of sustainability of crop production systems in the biome of the Brazilian Amazon. The experiment carried out in the municipality of Alta Floresta - MT started in August 2012. The technical approach of the project was based on Good Agricultural Practices (GAP) and included the evaluation of the impacts resulting from the implementation of administrative and economic management within farms. A selection of six beef cattle farms was carried out where technical and economic data were collected during the years of 2013 and 2014. Diagnoses were carried out through the application of questionnaires addressing the managerial capacity of the producer, level of technical knowledge, adoption of technologies on property, sanitary, reproductive management, food management, types of supplements provided, water conditions, animals and structures and, in sequence, elaborated projects of technical and economic feasibility. In addition, a complementary study was carried out to evaluate enteric methane emissions in the intensified systems, in Technological Reference Units (URT) and in areas of low productivity pasture (SDR). The period of the year had an influence on beef cattle production and on grazing costs in intensified areas. The intensification of production systems coupled with the Good Agricultural Practices (GAP) provided better indicators of efficiency of production systems, when compared to the farm that did not adopt GAPs, as an increase in gross margin per hectare, presenting a value of R $ 749.39. There was also a 16% increase in live weight production per hectare, 2.05% in the IRR and R $ 335.92 in the Net Present Value (NPV) between 2013 and 2014. Methane emissions per kilo of (gCH4-1.kgPV-1) were 38.18% lower in intensified systems, based on higher productivity pastures (URT). Social gains could be verified in the questionnaires answered, according to the set of aspects that favored the development of the worker as a human being, and in an expanded way as a person, professionally and socially. This increase was verified with a better evaluation of the knowledge of the process throughout the implementation of good practices and the verification of the benefits obtained to the productive system. In addition, the increase in technical coefficients highlighted a more favorable scenario, maintaining the producer in the activity, generating new jobs and obtaining better economic returns of the activity. The adoption of Good Agricultural Practices favorably impacted the environmental, technical-economic and social indicators in systems of production of beef cattle in the Brazilian Amazon. The integrated and more intensified production systems of beef cattle breeding in the Cerrado and the Amazon have proved to be more efficient and sustainable